Musahibahi-yi bultani khabari-yi Kurdistan : (Hizbi Dimukrati Kurdistani Iran, 1985)
An interview conducted by the News Bulletin of Kurdistan with a comrade of the Political Bureau and the representative of the Democratic Party of Iranian Kurdistan abroad.